NILAI MORAL DALAM NOVEL DEAR ALLAH KARYA DIANA FEBI (KAJIAN ANALISIS ISI) - Putri Yani; Sumiharti Sumiharti; Uli Wahyuni (Universitas Batanghari, 2021)
This research is qualitative descriptive research. Qualitative descriptive research aims to describe the form of moral values in the form of words and language from research results in a novel. The novel's data is in the form of quotations of words, sentences, and paragraphs in the novel Dear Allah by Diana Febi. The results show moral values, namely moral values in human relationships themselves, human relationships with other human beings in the social sphere with the natural environment, and human relationships with God. The moral value of a human relationship with oneself is patience, sincerity, responsibility, and courage. The moral value of a human relationship with other human beings in the social sphere with the natural environment is social care, friendship, compassion, forgiveness, help, and tolerance. The moral value of man and his God is gratitude, faith, and prayer.